Prevalence of oral submucous fibrosis, its correlation of clinical grading to various habit factors among patients of Bihar: A cross sectional study - Priya Rani; Rana N P. Singh; Swati Sharma; Ajoy K Shahi; Subhash Chandra; Bishnupati Singh (Wolters Kluwer Medknow Publications, 2023)
Aim: To find out the prevalence of OSMF and its Co-relation of clinical grading to various habit factors (time span of habit practiced in years, repetition of habit practiced per day, time of habit practiced in minutes per use). Method: This descriptive, cross-sectional survey was carried out and close ended questionnaire was used for data collection. Demographic details like gender & age and different tissue exploiting habits like, chewing gutkha, chewing areca nut, chewing panmasala with or without tobacco, plain tobacco, mawa, smoking, alcohol was recorded. Also, duration of habit in years, repetition of habit per day, time of habit per use & site of involvement was recorded. Results: Among 5297 patients examined at OPD, 120 were diagnosed with OSMF. The present study found no statistical relation between age, gender & OSMF. The present study concluded that majority 83 (69.17%) of the OSMF patients are guthka user and buccal mucosa was most affected site. OSMF was more prevalent in patients who practiced the habit for more than 15 years. Conclusion: Among the OSMF patients, guthka was most commonly practiced & buccal mucosa was most commonly involved. Duration and frequency of consumption were significantly associated with severity of OSMF.